Pengaruh kuliah praktisi pada mk kimia polimer terhadap capaian pembelajaran, motivasi dan minat belajar mahasiswa - Musawwa, Muhammad Miqdam Musawwa (Universitas Islam Indonesia, 2024)
Chemistry is a field of science that is the basis for the development of science and technology. Many technological innovations come from chemical research, not least in the field of polymers. Polymer Chemistry Course (MK-KP) is one of the compulsory courses in UII Chemistry Study Program. In this study, practitioner lectures were organized for MK-KP with the aim of increasing students' knowledge of the latest technology, polymer applications in the industrial sector. Practitioner lectures were held as many as 7x online meetings. The lecture involved a practitioner from one a polymer company in Bekasi as an industrial partner of UII Chemistry Study Program. The effect of this lecture was evaluated on the achievement of CPMK, student interest and motivation in MK-KP. The results showed that all students succeeded in achieving the CPMK MK-KP. Students also showed high interest and motivation in attending practitioner lectures with a percentage of 75% and 81% respectively. This research supports online practitioner lectures to be implemented in other courses.